PEMBELAJARAN BAHASA ARAB MELALUI MODEL AKTIF LERNING PADA SEKOLAH DASAR ISLAM TERPADU AL-FURQON PALEMBANG - Adriyanto Adriyanto (Conciencia, 2015)
Active learning, creative, effective and fun in the Arabic language lessons in elementary school performed Islam al-Furqan Palembang with the problem is the implementation of active learning, creative, effective and fun in learning Arabic in elementary school Isam Al-Furqan Palembang, and Implications active learning, creative, effective and fun in learning Arabic and uncover Advantages and drawbacks in active learning, creative, effective and fun in Arabic language lessons in primary school Isam Al-Furqan Palembang. This research is a field that seeks to collect data with a qualitative approach and collected through observation of all activities related to the research, documentation also performed well against some archives Elementary School Isam Al-Furqan Palembang, data is also collected through a series of interviews with language teachers Arab. The triangulation in this research is triangulation sources that can compare the results of interviews with the contents of a document in this study. The data collected is then analyzed by descriptive qualitative, ie by reduced, dikatagorisasi, classified, and further described in accordance with the research problem. The research found that, Applying (PAKEM) in Arabic language lessons in primary school Isam Al-Furqan Palembang, implemented on the indicator. This can be seen from the implementation of indicators on active learning, creative, effective, and fun in learning Arabic. Lessons and implications (FAKEM) on Arabic in elementary school Isam Al-Furqan Palembang, either in facilities, learning tools, learning infrastructure, learning resources and instructional media, environmental regulation, the classroom setting, and activities, as well as the learning environment has created a fun learning atmosphere. In (FAKEM) has advantages and disadvantages in the Arabic language learning in primary school Isam Al-Furqan Palembang, it is seen from its superiority can provide freedom in learning and makes the classroom atmosphere is dynamic and alive, where each teacher and students equally active, where each teacher and student same- equally active. And weaknesses, teachers can not always active, and teachers also have not been able to properly condition the classroom, and teachers do not understand the nature of the student.